Compulsory Health Insurance: The Economic Issues - Campbell, Rita Ricardo; Campbell, W. Glenn (Quarterly Journal of Economics, 1952)
I. Introduction, 1. — II. An analysis of the case for compulsory health insurance, 2. — III. An analysis of the case against compulsory health insurance, 11. — IV. Alternative methods of improving the nation's health, 19.